Effect of Long-term Moxibustion at Baihui (GV20) on Urinary Incontinence Patients with Cognitive Dysfunction after Stroke - Jun LENG; Fangyue WEI; Wen GUO; Huimin LIU; Xiaoxue LENG (康复学报)
Objective:To observe the effect of long-term moxibustion at Baihui (GV20) acupoint on urinary incontinence patients with cognitive dysfunction after stroke.Methods:A total of 80 cases of urinary incontinence patients with cognitive dysfunction after stroke were randomly divided to the control group and observation group, with 40 cases in each group. The control group received routine rehabilitation training, including cognitive function training, acupuncture, physiotherapy and massage, all patients were required to maintain 2 000-3 000 mL/24 h of drinking water during the whole study. The observation group received long-term moxibustion with pure moxa stick at Baihui acupoint on the basis of the control group, more than two hours per time, for as long as possible, and once per day, seven times per week, continuous treatment for eight weeks or till the end of treatment (disappearance of incontinence symptoms). At both the before treatment, and after treatment for eight weeks, the cognitive dysfunction score was evaluated by Mini-mental state examination (MMSE), the bladder urination function was evaluated by 24 hours of urination, bladder safety capacity, residual urine volume, the ability of daily living was evaluated by the modified Barthel index (MBI).Results:After treatment for eight weeks, the MMSE, MBI scores, single urine output, bladder safety capacity of the control group were (21.86±2.41) scores, (57.30±7.33) scores, (124.41±24.35) mL a time, (215.11±17.86) mL, and the observation group were (23.08±2.62) scores, (60.53±6.37) scores, (179.29±18.23) mL a time, (264.21±20.05) mL. Compared with before treatment, the MMSE, MBI scores, single urine output, bladder safety capacity of both groups after treatment for eight weeks were higher, and the improvement in the observation group was significantly higher than that of the control group (P<0.05). After treatment for eight weeks, the urine frequency, frequency of urinary incontinence, residual urine volume in the control group were (11.84±2.28) times a day, (6.59±1.94) times a day, (124.16±31.74) mL, and the observation group were (8.95±2.34) times a day, (5.13±1.86) times a day, (95.82±35.24) mL. Compared with before treatment, the urine frequency, frequency of urinary incontinence, residual urine volume of both groups after treatment for eight weeks were lower, and the decrease degree in the observation group was significantly better than that of the control group (P<0.05).Conclusion:Long-term moxibustion at Baihui acupoint can improve the cognitive function, increase the bladder safety capacity, reduce urinary incontinence and improve the ability of daily life of patients with urinary incontinence after stroke.